Flexible Working Arrangements and Subjective Career Success: Coping Mechanisms as Mediator during the COVID-19 Pandemic: - - Hartanto, Alysia; Nilawati, Levi; Nugroho, Yohanes Arianto Budi (Bina Nusantara University, 2024)
The research aimed to examine the effect of Flexible Working Arrangements (FWA) on subjective career success (SCS) with the mediation of coping mechanisms (social support, active coping, and identity awareness) among employees during the COVID-19 pandemic. The research investigated whether coping mechanisms can act as a mediator when a work policy supports their employees during uncertain times through working from home to improve long-term health and well-being. The research was conducted in the e-commerce companies in Jakarta with a convenience sample of 205 respondents. The analysis was conducted empirically using Macro Hayes to examine the mediating role of coping mechanisms on the relationship between FWA and SCS. The results indicate that FWA has a significant positive effect on coping mechanisms. Coping mechanisms (social support and active coping) have a significant positive effect on SCS, except for identity awareness. FWA does not have a direct effect on SCS. Moreover, coping mechanisms (social support and active coping) mediate the relationship between FWA and SCS, except for coping mechanism (identity awareness), which does not have a significant effect. The research emphasizes the importance of coping mechanisms, namely social support and active coping, and calls for future researchers to pay more attention to coping mechanisms as countermeasures during a pandemic-induced public health crisis.